Access to Liquidity and Corporate Investment in Europe during the Financial Crisis - Campello, Murillo; Giambona, Erasmo; Graham, John R.; Harvey, Campbell R. (Review of Finance, 2012)
Abstract We use a unique data set to show how firms in Europe used credit lines during the financial crisis. We find that firms with restricted access to credit (small, private, non-investment-grade, and unprofitable) draw more funds from their credit lines during the crisis than their large, public, investment-grade, profitable counterparts. Interest spreads increased (especially in “market-based economies”), but commitment fees remained unchanged. Our findings suggest that credit lines did not dry up during the crisis and provided the liquidity that firms used to cope with this exceptional contraction. In particular, credit lines provided the liquidity companies needed to invest during the crisis.